Explaining Trump's Popular Support: Validation of a Nativism Index. (28th January 2019) - Young, Clifford; Ziemer, Katie; Jackson, Chris
Abstract : Objective: In this article, we describe the development of a Nativism Index and evaluate its validity in the U.S. context, a global sample, and over time. Our overall objective is to establish the Nativism Index as a valid and reliable measure of nativism for use in subsequent research. Method: Using survey data from Ipsos Public Affairs in the United States and from the Ipsos Global Advisor for our global sample, we test the convergent and discriminate validity and reliability of the Nativism Index. Results: The Nativism Index is correlated with but clearly distinct from related concepts, including populism, authoritarianism, and fear of others. The Nativism Index is also predictive of support for Donald Trump in the United States and UKIP in the United Kingdom. Conclusion: Overall, our findings suggest that the Nativism Index represents a robust measure with strong internal consistency and high convergent and divergent validity in both U.S. and global samples.